2017
DOI: 10.1097/mpa.0000000000000921
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Node Metastasis in the Prognosis of Gastroenteropancreatic Neuroendocrine Tumors

Abstract: Objectives This study aimed to determine the prognostic utility of the extent of lymph node involvement in patients with gastroenteropancreatic neuroendocrine tumors (GEP-NETs) by analyzing population-based data. Methods Patients in the Surveillance, Epidemiology, and End Results (SEER) registry were identified with histologically confirmed, surgically resected GEP-NETs. We divided patients into three lymph node ratio (LNR) groups based on the ratio of positive lymph nodes to total lymph nodes examined: ≤0.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 22 publications
(14 reference statements)
0
18
0
Order By: Relevance
“…In this analysis, patients with a LNR >0.2 had a 5‐year DFS of 46% versus 76% for patients with a LNR ≤0.2 . Similarly, Martin et al reported an increased risk of death of 1.5‐, 2‐, and 3‐fold for patients with LNR ≤0.2 (HR, 1.5), LNR 0.2‐0.5 (HR, 2.0), and LNR >0.5 (HR, 3.1), respectively, compared with patients without nodal metastasis . In the current analysis, the number of metastatic nodes was also strongly associated with the risk of recurrence on both univariable and multivariable analyses.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…In this analysis, patients with a LNR >0.2 had a 5‐year DFS of 46% versus 76% for patients with a LNR ≤0.2 . Similarly, Martin et al reported an increased risk of death of 1.5‐, 2‐, and 3‐fold for patients with LNR ≤0.2 (HR, 1.5), LNR 0.2‐0.5 (HR, 2.0), and LNR >0.5 (HR, 3.1), respectively, compared with patients without nodal metastasis . In the current analysis, the number of metastatic nodes was also strongly associated with the risk of recurrence on both univariable and multivariable analyses.…”
Section: Discussionmentioning
confidence: 61%
“…While data on overall survival has more commonly been reported, the risk of recurrence following curative resection of primary NET has been less defined. Specifically, data on recurrence after resection, including incidence of recurrence, recurrence pattern and prognostic factors associated with recurrence, remain relatively scarce . Data on recurrence is, however, important to inform patients about the likelihood of treatment success and the risk of recurrence following surgical intervention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This binary staging differs from lymph node staging for almost all other solid tumors such as rectal adenocarcinomas, which have multiple categories based on the number of lymph nodes involved . Previous studies have shown that the number of positive lymph nodes is linked with NET prognosis . However, no studies to date have evaluated the independent prognostication for lymph node positivity in rectal NETs.…”
Section: Introductionmentioning
confidence: 98%
“…These tumours are biologically heterogeneous, and outcomes can similarly vary, depending on the status of tumours. 16 To the best of our knowledge, for g-NET, this is the first study to include treatment strategies (surgery, chemotherapy and radiotherapy) into prognostic analysis and nomograms. Considering the importance of LNR, we included LNR in the nomogram.…”
Section: Discussionmentioning
confidence: 99%